Kualitas Fungi Mikoriza Arbuskula (FMA) yang Diproduksi dengan Teknik Fortifikasi dan Fertigasi Berbeda pada Pertumbuhan Indigofera zollingeriana - Iwan Prihantoro; Panca Dewi Karti; Edit Lesa Aditia; Shandathyana Nisabillah (Institut Pertanian Bogor, 2023)
Arbuscular mycorrhizal fungi (AMF) is a fungus that has a symbiotic impact on the plant at the root system level. The research objective was to evaluate the growth of Indigofera zollingeriana produced from inoculation of AMF under different fortification and fertigation techniques at the field scale. A completely randomized design with six treatments and five replication were applied for the study. The treatments were: FD1000, FD2000, FD3000 (AMF fortified with 1000, 2000, and 3000 ppm of AB mix at flat fertigation), FB1000, FB2000, and FB3000 (AMF fortified with 1000, 2000, 3000 ppm of AB mix at graded fertigation). The result shows that the AMF colonization level at the root of was similar (P>0.05) to the upper value of colonization (80.00‒99.00%). The entire products of AMF have similar favorable symbiotic effects on the plant with major growth traits (plant high, stem diameter, number of branches and twigs). A fortification of 2000 ppm of AB mix under graded fertigation technique has produced AMF that significantly (P<0.05) increased the number of leaves with higher green color level (7.5GY 4/6) compared with other treatments. In conclusion, the AMF produced by different fortification and fertigation techniques at the field scale has a similar result on root colonization effectivity and growth performance of I. zollingeriana. In addition, the AMF produced by 2000 ppm of AB mix with graded fertigation technique effectively increased the number of leaves with higher green color intensity. Keywords: AMF, arbuscular mycorrhizal fungi quality, fertigation, fortification, Indigofera zollingeriana